Optimization of assay conditions to quantify ECOD activity in vivo in individual Daphnia magna. Assay performance evaluation with model CYP 450 inducers/inhibitors - András Ács; Attila W. Kovács; János Győri; Anna Farkas (Ecotoxicology and Environmental Safety, 2024)
Screening the activity of the cytochrome P450 (CYP450) mixed function oxidase system in aquatic invertebrates received seldom applications in ecotoxicology due to low baseline enzymatic activities characteristic for these organisms. In this study, an existing in vivo spectrofluorometric assay method based on quantifying the cytochrome P450 mediated conversion of 7-ethocycoumarin (EtC) used as substrate to the product 7-hydroxycoumarin (HCm) called: ethoxycoumarin-O-deethylase (ECOD) activity, initially applicable on pooled samples of Daphnia magna, was optimized for use on individual organisms. Optimal assay conditions have been established for as small as 3- and 6 days old individuals, and the limits of spectrofluorometric detection of HCm excreted by daphnids in the incubation media were defined. The modified assay was tested by screening the modulation of ECOD activity in daphnids following 24 h exposure to β-naphthoflavone (β-NF, reference CYP450 inducer) and to prochloraz (PCZ), a potent CYP450 inhibitor. Maximal ECOD activity levels in daphnids were recorded following 2 hours of incubation to 200 nM EtC. The limit of spectrofluorometric detection of HCm in the incubation media was 6.25 nM, achieved by more than 80% of three days old daphnids and all six days old individuals. Exposure of daphnids to β-NF demonstrated a bell-shaped ECOD activity induction potential, while PCZ elicited partial (60%) inhibition of ECOD activity. This optimized in vivo ECOD activity assay may serve as a cost-effective tool to study the responsiveness of Phase-I metabolism in D. magna to toxic pressure and its applicability to other aquatic invertebrates is also worth for consideration.